Strategic Educational Marketing in Islamic Educational Institutions: Managing Institutional Growth and Sustainability - Yulianto; St. Rodliyah; Gunawan (Educazione: Journal of Education and Learning, 2025)
Islamic higher education institutions increasingly face pressure to compete, respond to shifting stakeholder expectations, and remain viable over the long term, yet educational marketing is still widely treated as promotion rather than a strategic management function. This study examines how strategic educational marketing is planned, implemented, and sustained to support institutional growth and sustainability. A qualitative case study guided the research. Data came from semi-structured interviews, non-participant observation, and document analysis involving university leaders and key administrative stakeholders, collected between May and July 2026, and were analyzed through the interactive model of Miles, Huberman, and Saldaña, with credibility secured through triangulation and member checking. The findings indicate that marketing planning integrates environmental analysis, stakeholder engagement, institutional branding, and segmentation, targeting, and positioning within the university governance system. Implementation combines digital platforms, school visits, partnerships, alumni engagement, and community outreach to strengthen visibility and stakeholder relationships, while sustainability rests on reputation, trust, continuous quality improvement, and internationalization. Rather than a promotional tool, strategic educational marketing operates as an integrated governance capability that carries the institution through transformation while preserving its Islamic identity. These results imply that university leaders should embed marketing within governance and quality assurance to achieve sustainable institutional development.